The Concrete Quality Testing for Trapezoidal Model of the Prefabricated Foundation - ., Koespiadi; Wiwoho Mudjanarko, Sri; Rasidi, Nawir; Mulyo Utomo, Wahyu; Alimudin, Arasy; Supriyatno, Dadang; Haksama, Setya; Farid Dimyati Lusno, M; Bin Madun, Aziman; Pratama Wiwoho, Firdaus; Wahyu Pamungkas, Jackson; Daniel Limantara, Arthur (International Journal of Engineering and Technology, 2018)
The foundation made of the stone material is widely used in the construction of houses in Indonesia. The need and limitations of stone materials as the basic ingredients of foundation building need innovative thinking of its development. This study aims to develop a substitute foundation made of stone with the foundation of precast concrete. Precast concrete foundation model developed with varied models. The methodology is to make varied models of trapezoidal precast foundation with the inside of the perforated part. The precast foundation model is very easy to do and practical. The conclusions show that the precast foundation is capable of accepting the expected and feasible loads used for house building foundationsÂ